2015
DOI: 10.1007/s11845-015-1283-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis to identify a key role of CDK1 in mediating gene interaction networks in cervical cancer development

Abstract: CDK1 plays a comprehensive role in mediating genetic networks implicated in the progression of cervical cancer. Novel therapeutics targeting CDK1 or its related pathways might help improve prognosis of advanced stage cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Abnormal cell proliferation and genomic instability were caused by dysregulation of CDKs . According to our integrated analysis, up‐regulated CDK1 was modulated by hsa‐miR‐205 and hsa‐miR‐24 in the tissues of CIN versus N and by hsa‐miR‐195 and hsa‐miR‐497 in CIN versus CSCC, which have the same pattern in a previous study . In the PPI analysis, CDK1 has the highest degree among the hub proteins.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Abnormal cell proliferation and genomic instability were caused by dysregulation of CDKs . According to our integrated analysis, up‐regulated CDK1 was modulated by hsa‐miR‐205 and hsa‐miR‐24 in the tissues of CIN versus N and by hsa‐miR‐195 and hsa‐miR‐497 in CIN versus CSCC, which have the same pattern in a previous study . In the PPI analysis, CDK1 has the highest degree among the hub proteins.…”
Section: Discussionsupporting
confidence: 74%
“…Also, CDK1 was enriched in the p53 signaling pathway in the KEGG analysis. Luo et al [16] reported that CDK1 played a complicated role in regulating genetic networks involved in the progression of cervical cancer. Prognosis of advanced stage cervical cancer may be enhanced by new therapeutics targeting CDK1 or its related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1 is one of the serine/threonine kinases that regulate the cell cycle by interacting with specific cell-cycle-regulatory cyclins (22). It has been reported that CDK1 regulated CC (23).It is also involved in the proliferation of many tumors. Y. Zeng et al found that Cyclin-dependent kinase 1 (CDK1)-mediated mitotic phosphorylation of the transcriptional co-repressor Vgll4 inhibits its tumorsuppressing activity.…”
Section: Discussionmentioning
confidence: 99%
“…is a member of the Serine/Threonine protein kinase family. Previous studies showed that CDK1 was related to many types of tumors growth and the patients survival [17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%